High temperature heat accumulation and heat exchange device for solar thermal power generation - CUI HAITING; JIANG JINGZHI; ZHOU HUITAO (2012)
The utility model discloses a high temperature heat accumulation and heat exchange device for solar thermal power generation. The high temperature heat accumulation and heat exchange device comprises a heat accumulation device box body and a high temperature phase transition heat accumulation pipe which is placed in the heat accumulation device box body in parallel connection mode. A base and a top cover are respectively arranged at two ends of the heat accumulation device box body. An inlet pipe and an outlet pipe of fluid are arranged on the box body. A spoiler is arranged in the box body to improve perturbation of the fluid on the spoiler side and strengthen heat exchange of the fluid on the spoiler side. The high temperature phase transition heat accumulation pipe is a ceramic steel composite tube, wherein phase transition heat accumulation materials are filled in the high temperature phase transition heat accumulation pipe, and ring-shaped fins are arranged outside the high temperature phase transition h